2012
DOI: 10.4103/0972-9941.103121
|View full text |Cite
|
Sign up to set email alerts
|

Two-port vs. three-port laparoscopic appendicectomy: A bridge to least invasive surgery

Abstract: INTRODUCTION:The conventional three-port technique for laparoscopic appendicectomy has proven its worth in the management of appendicular pathologies. From a cosmetic viewpoint, the umbilical and suprapubic port-sites are hidden by natural camouflages, the right Iliac fossa (RIF) port is the only visible external sign of surgery. The two-port technique avoids even this marker of abdominal invasion. In this study, we describe the technique of two-port laparoscopic appendicectomy (TPA) and compare it with conven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 16 publications
2
10
1
Order By: Relevance
“…2 TLA has an advantage over SILS and NOTES in being safe, easy, feasible, not requiring specialized instruments and also economical. 11 TLA is a safe and feasible in children with the operative time and post-operative complications being the same to that of CLA. 12 CONCLUSION: Two port Laparoscopic appendicectomy is safe, cost-effective, cosmetically effective, easy to learn and perform.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 TLA has an advantage over SILS and NOTES in being safe, easy, feasible, not requiring specialized instruments and also economical. 11 TLA is a safe and feasible in children with the operative time and post-operative complications being the same to that of CLA. 12 CONCLUSION: Two port Laparoscopic appendicectomy is safe, cost-effective, cosmetically effective, easy to learn and perform.…”
Section: Discussionmentioning
confidence: 99%
“…10 Two-port Laparoscopic Appendectomy (TLA) has all the advantages of Conventional Laparoscopic Appendectomy (CLA) with significantly reduced operative time and cost. Ours is modified technique of Ashwin Rammohan et al 11 The needle with loop retractor has an added merit of holding the appendix even with extensive inflammation, enables the surgeon for stable manipulation and gives better counter-traction than conventional forceps 11 . Also with the intraoperative view the surgeon can decide the best site for placement of the needle-loop which is ergonomically and cosmetically suitable 11 .…”
Section: Discussionmentioning
confidence: 99%
“…However, SILS has several limitations: it is difficult to perform, requires a bigger umbilical incision, carries a high risk of port-site incisional hernia, has a longer duration of surgery, and presents a steep learning curve (8,9,13). As a bridge between CLA and SILS, numerous studies have been done in which the number of ports has been reduced; they have also compared CLA and SILS to port exteriorization appendectomy, needlescopic appendectomy, extracorporeal appendectomy, laparoscope-assisted appendectomy, and needle loop retractor appendectomy (6,(14)(15)(16). The present study similarly compared CLA to DILA, but there was no reduction in the number of ports.…”
Section: Discussionmentioning
confidence: 99%
“…In the CLA group, 55.2% of the patients were women, and in the DILA group, 64.5% were; this difference was not statistically significant (P = 0.460). In a study that used a hypodermic needle to extracorporeally ligate the base of the appendix, Rammohan et al reported a higher proportion of women (55%) than men (16). In a study of 248 patients comparing single-port LA to CLA, 37.9% of patients had acute appendicitis and 32.6% had acute suppurative appendicitis (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation